Cellulose Compound of Cacao Waste and Chemical Composition of Cacao Vinegar with GC-MS Method - Mohammad Wijaya. M; Muhammad Wiharto; Muhammad Anwar (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2017)
Potential of cacao resources at Indonesian is very dependent on the production of cacao produced by farmers and plantation availability. However, the cacao processing results are still not optimal to increase the cacao production. This is due to the disruption of pests and the number of cacao farmers over land functions for fast growing plants. Processing cacao produced cacao waste and with the use of pyrolysis technology is able to cope with the accumulation of plantation waste. This combustion results in liquid smoke of cacao (cacao vinegar) into distillate, charcoal. This study used pyrolysis temperature between 100-500 °C. The aim of this research is to analyze the cocoa waste and the results are cellulose content 17,27%, lignin 52,02% and hemicellulose 19,56%. The results of GC-MS analysis for cacao vinegar of Distric Wajo are acetic acid, n butane, methyl ester, propanoic acid, butanoic acid, cyclopenanone, 2 methyl pyridine, acetyloxy 2 propanone, butyrolactone, tetrahydro 2 furan methanol, 2,3 dimethyl 2 cyclopentene 1 on and Mequinol. The water content of the charcoal of cacao shell from Wajo district is 3.42%. The analysis results of the bound carbon content of activated charcoal of cacao shell is 54.45%. The EDS analysis for cacao shell from Wajo district resulted in C: 61.12%, O: 36.65%, Si: 0.59%, P: 1.48% and Al: 0.17%. Utilization of cocoa shell waste using pyrolysis technology can reduce carbon emissions to the environment. So that the development of everything can continue and the sustainability of forest remain sustainable.